Investigation of dgat1 and prnp gene polymorphism of various cattle breeds in turkey - İclal Şahin; Zafer Bulut; Ercan Kurar; Yusuf Özşensoy; Müge Doğan; Mehmet Nizamlıoğlu (Eurasian Journal of Veterinary Sciences)
Aim: In the present study, DGAT1 gene K232A and promoter and intron 1 indel polymorphisms of PRNP gene were studied. Materials and Methods: Samples were collected a total of 122 animals including Turkish Grey (AG), Anatolian Black (AB), South Anatolian Red (SAR), East Anatolian Red (EAR) ve Zavot breeds were used for the study. The samples were genotyped for DGAT1 K232A polymorphism (A and K allel) using the polymerase chain reaction-restriction fragment lenght polymorphisms (PCR-RFLP) technique. PRNP gene polymorphism in the promoter (23 bp indel) and intron 1 regions (12 bp indel) were determined by PCR analysis. Results: The highest frequency of A allele in DGAT1 gene was found in the AG (0.58), followed by SAR and Zavot (0.50), AG and EAR showed the lowest frequencies of A allele (0.38). The highest frequency of del/del genotype in promoter region of PRNP gene was found in the EAR and SAR (0.53 and 0.52, respectively) followed by AG (0.46); however, AB (0.19) and Zavot (0.17) showed the low frequencies. In intron 1 region of PRNP, the highest frequency of del/del genotype was found in the AG (0.25) and EAR (0.13), followed by AB (0.08). The lowest frequency (0.05) of del/del genotype was observed in EAR and Zavot. Conclusion: Results of the present study on AG, AB, SAR, EAR and Zavot breeds could be used to guide association studies between DGAT1 and PRNP gene polymorphisms may be useful for selection of milk traits on animal husbandry and reclamation studies.